Exosomes: an innovative therapeutic target for cerebral ischemia-reperfusion injury - Yang, Yuan; Duan, Yushan; Yue, Jinxi; Yin, Yue; Ma, Yiming; Wan, Xiaohong; Shao, Jianlin (Frontiers in Pharmacology, 2025)
Ischemic stroke is caused by artery stenosis or occlusion, which reduces blood flow and may cause brain damage. Treatment includes restoring blood supply; however, ischemia-reperfusion can still aggravate tissue injury. Reperfusion injury can increase levels of reactive oxygen species, exacerbate mitochondrial dysfunction, create excessive autophagy and ferroptosis, and cause inflammation during microglial infiltration. Cerebral ischemia-reperfusion injury (CIRI) is a key challenge in the treatment of ischemic stroke. Currently, thrombolysis (e.g., rt-PA therapy) and mechanical thrombectomy are the primary treatments, but their application is restricted by narrow therapeutic windows (<4.5 h) and risks of hemorrhagic complications. Exosomes reduce CIRI by regulating oxidative stress, mitochondrial autophagy, inflammatory responses, and glial cell polarization. In addition, their noncellular characteristics provide a safer alternative to stem cell therapy. This article reviews the research progress of exosomes in CIRI in recent years.